THE INFLUENCE OF INDEPENDENCE, AUDIT EXPERIENCE, TYPES OF PERSONALITY TO PROFESSIONAL SKEPTICISM AND FRAUD DETECTION ABILITY OF AUDITORS (Empirical Study at Accounting Public Office in Big Four Indonesian) - VILLA AULIA (Jurnal Ilmiah Mahasiswa FEB, 2018)
This study was aimed to examine the influence of independence, audit experience, typesof personality to professional skepticism and fraud detection ability of externalauditors. The Hurtt, Eining, dan Plumlee model (2010) is used to classify auditors aseither high or low skepticism. Myers Briggs Type Indicator (MBTI) is used for classifyauditors as type of personality ST (Sensing-Thinking) and NT (Intuitive-Thinking) orother. Ability to detection fraud is measured by fraud symptoms from Fullerton andDurtschi (2004). Respondent of this study was collected through questionnairesdistributed to 120 auditors who work at Accounting Public Office in Big FourIndonesian. Data were collected using convenience sampling technique. The tool usedto analyze for hypothesis is Partial Least Square (PLS) with the SmartPLS application.The results of this study give evidence that independence and types of personality haveeffect toward professional skepticism; didn’t find effect of audit experience towardprofessional skepticism; audit experience and professional skepticism have effecttoward fraud detection ability of auditors; didn’t find effect of independence and typesof personality toward fraud detection ability of auditor. The value of adjusted R squarefor fraud detection ability of auditors is 10,6% and professional skepticism is 72%.Keywords: Independence, Audit Experience, Types of Personality, ProfessionalSkepticism and Fraud Detection Ability of Auditor.